Development and Application of a Program for Reinforcing Global Health Competencies in University Nursing Students - Hwang, Won Ju; Jo, Hyun Hee (Frontiers in Public Health, 2020)
Purpose: With globalization, the importance of global health is being stressed. Although nurses are indispensable healthcare professionals, programs to develop nurses with global health competencies and relevant studies are rare. Accordingly, the purpose of this study was to develop a program to increase global health competencies and global leadership in nursing students and test the effect of the program. Methods: A single group pre-and post-test study design was used. A 13-week program was developed and applied to 204 subjects. Data were analyzed using paired t-test. The program to promote global health competencies was designed to improve nursing students' knowledge of global health, global leadership, global health competencies, critical thinking ability, and student-student partnership. Results: Global health competencies (t=-19.96, p<.001), self-assessed global leadership (t=-7.67, p<.001), and critical thinking (t=-7.67, p<.001) were all significantly increased. Discussion: The study findings of increased global health competencies and global leadership in nursing students after participation in the program indicated ways in which global health competencies of nurses need to be developed. Therefore, the following aspects should be considered. First, nursing educators should understand the need and importance of global health education and based on this understanding, the current curriculum should be revised to include courses on global health. A systematic course of studies on global health should be developed and applied based on discussions among experts and diverse research studies. Second, as future healthcare professionals, nursing students should take interest in global health problems, and recognize various issues that need to be solved beyond borders between countries. To develop global health competencies, various efforts and systematic curriculum would be necessary.